2014
DOI: 10.1177/2153368714534269
|View full text |Cite
|
Sign up to set email alerts
|

Race, Space, and Being Policed

Abstract: Research on race and policing has consistently documented the link between race, space, and policing with racial disparities in perceptions and experiences often explained by nature of policing within low-income, distressed communities of color. This study adds a new dimension to past research by examining the relationship between race, racial composition of place, and residents’ experiences with southern police across public and semipublic spaces within a middle-class, low-crime, tourism-driven resort area. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Surveillance and policing of white spaces and white properties, especially by white men, have been a constant cultural and institutional practice (Bonner, 2014). Being white and perceived as white in these spaces have granted white men (and white women) the spatial privilege (Kunst et al, 2018) to move freely.…”
Section: Surveilling Policing and Taking Up White Spacementioning
confidence: 99%
“…Surveillance and policing of white spaces and white properties, especially by white men, have been a constant cultural and institutional practice (Bonner, 2014). Being white and perceived as white in these spaces have granted white men (and white women) the spatial privilege (Kunst et al, 2018) to move freely.…”
Section: Surveilling Policing and Taking Up White Spacementioning
confidence: 99%
“…In high-crime areas where stops and searches were heavily deployed, citizens were found to be less likely to report a crime to the police (Tyler et al, 2014). Furthermore, rates of citizen complaints about police use of stop and search were higher among those who lived in more economically underprivileged, minority areas (Bonner, 2014; Rengifo & Fowler, 2016). Lastly, a longitudinal study of adolescents’ experiences with police stops and criminal behavior conducted by Del Toro et al (2019) revealed that Black and Latino boys who experienced police stops reported more frequent involvement in delinquent acts 6, 12, and 18 months later.…”
Section: Review Of Literature and Hypothesesmentioning
confidence: 99%
“…Studies have shown that Blacks and Hispanics are more likely than non-Hispanic Whites to be subject to more intensive law enforcement practices (Arnio 2021;Lautenschlager and Omori 2019;Siegel et al 2019). Explanations for such racial/ethnic disparities have focused on the minority threat hypothesis (Roh and Robinson 2009), which suggests a higher likelihood of social control (i.e., policing) among those living in lower-income and distressed communities of color (Bonner 2014), with higher rates of poverty, higher residential segregation (Sytsma 2015), and higher levels of violent crime.…”
Section: Introductionmentioning
confidence: 99%